2021
DOI: 10.1093/rb/rbab017
|View full text |Cite
|
Sign up to set email alerts
|

The biological responses and mechanisms of endothelial cells to magnesium alloy

Abstract: Due to its good biocompatibility and degradability, magnesium alloy (Mg alloy) has shown great promise in cardiovascular stent applications. Rapid stent re-endothelialization is derived from migrated and adhered endothelial cells (ECs), which is an effective way to reduce late thrombosis and inhibit hyperplasia. However, fundamental questions regarding Mg alloy affecting migration and adhesion of ECs are not fully understood. Here, we evaluated the effects of Mg alloy on the ECs proliferation, adhesion and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[ 23 ] Rac Family Small GTPase 1 (RAC 1) and Ras Homolog Family Member A (Rho A) are essential Rho GTPases that regulate cell motility. [ 24 ] The higher expression of RAC 1 and Rho A further confirmed that ECs had a high migration ability on the A45R1 coating. The rapid migration of ECs to the material surface accelerates endothelialization.…”
Section: Resultsmentioning
confidence: 81%
“…[ 23 ] Rac Family Small GTPase 1 (RAC 1) and Ras Homolog Family Member A (Rho A) are essential Rho GTPases that regulate cell motility. [ 24 ] The higher expression of RAC 1 and Rho A further confirmed that ECs had a high migration ability on the A45R1 coating. The rapid migration of ECs to the material surface accelerates endothelialization.…”
Section: Resultsmentioning
confidence: 81%
“…This was further supported by the decreased expression of Ki67, which serves as a cell proliferation indicator (Figure S46). 33 Meanwhile, the cytocidal ability of DBQ-2DPA NPs, DBQ-2TPA NPs, and DBQ-4TPA NPs was also assessed through the CCK-8 assay. As anticipated, DBQ-2DPA-4TPA NPs revealed superior phototoxicity toward A375 cells compared to the other AIE NPs, which can be attributed to its higher ROS generation ability (Figure S47a−c).…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting was conducted as described previously [ 25 ]. All experiments were quantified by Image lab (Bio-Rad) and normalized to internal control.…”
Section: Methodsmentioning
confidence: 99%